Faktor Resiko Penyakit Kardiovaskular Dari Kegiatan Donor Darah - Irfan Sazali Nasution; Mulyani Mulyani; Dhea Triana Dewi; Nadia Alhaq; Najma Hayati; Rabiul Zaman; Rizki Rizki (PT. Alahyan Publisher Sukabumi, 2024)
Blood donation is an activity that provides many benefits to both the recipient and the donor. Nonetheless, some health risk factors must be considered, especially cardiovascular health. This article aims to identify and discuss these risks. Anemia is one of the main risks, which can increase the heart's workload and potentially worsen cardiovascular conditions. A temporary drop in blood pressure after donation can also lead to impaired heart function in certain individuals. Infection at the needle puncture site, although rare, can lead to serious complications such as endocarditis. In addition, repeated blood donations without adequate fluid replacement can lead to electrolyte imbalances that affect heart rhythm. Decreased energy and physical performance after donation is also a concern. However, blood donation also has significant benefits, including reducing excessive iron levels in the blood and improving blood flow. Following medical guidelines and taking proper precautions can minimize these risks, making blood donation a safe and beneficial act for cardiovascular health. This article concludes that the benefits of blood donation far outweigh the risks if done correctly.